Phát triển thư viện số: những vấn đề cần xem xét - Cao, Minh Kiểm (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Outlines different concepts on digital library; makes clear the role and purpose of digital library; presents 7 problems to be considered when developing digital libraries of the Network of Excellence on Digital Libraries (DELOS): organization; content; users; ability; policy; quality; architecture.